2013
DOI: 10.1002/jsid.142
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dual mode reflective cholesteric display

Abstract: In this article, we report our study of a dual mode reflective cholesteric display, which works in the traditional bistable mode as well as in the new and fast monostable mode. Because both modes are compatible, they can be used according to the need for video or static images. The bistable mode operates between the reflecting planar state and non‐reflecting focal conic state, both of which are stable at zero voltage. The bistable mode is suitable for displaying static images. In the monostable mode, it is ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent study revealed that cholesteric displays can be used according to the need for static as well as video images [11]. For this type of display the cholesteric material preferably should consist of a nematic LC and a chiral dopant.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that cholesteric displays can be used according to the need for static as well as video images [11]. For this type of display the cholesteric material preferably should consist of a nematic LC and a chiral dopant.…”
Section: Introductionmentioning
confidence: 99%